Assessment of knowledge, attitude and practice towards athritis among nursing students in Universiti Sains Malaysia - Yunus, Nurmutiah Mohd (Universiti Sains Malaysia, 2024)
Arthritis and other rheumatic disorders were common diseases that caused pain, swelling, and limited mobility. They had an effect on the body's joints and connective tissue. There were over a hundred different types of arthritis, including rheumatoid arthritis, osteoarthritis, and other forms of arthritis or related disorders like gout, lupus, scleroderma, and many others. This research is aimed to assess knowledge, attitude, and practice towards arthritis among nursing students in Universiti Sains Malaysia (USM). A cross-sectional study design was conducted from 1st January 2024 to 31st March 2024 at the School of Health Sciences, USM. A total of 141 nursing students from degree and diploma were recruited via a purposive sampling method. Descriptive statistics and Pearson correlation test were used to analyse data. This study found that most of nursing students have heard about arthritis (94.3%) and their source of knowledge was from books and seminar (59%). The level of knowledge in this study showed that more participants experienced a high level of knowledge, with a mean score of 8.62 (SD = 2.36, range = 0–12). Besides, in this study mostly showed a high level of attitude, with a mean score of 22.14 (SD = 4.6, range = 0–24). The mean score for practice was 1.9 (SD = 0.12, range = 0-2), which indicates a positive practice towards arthritis. In this study, there is an association between level of knowledge and level of attitude with p- value less than 0.05 (p = 0.001), indicating that changes in knowledge levels were accompanied by corresponding changes in attitude levels. This study suggests that some basic knowledge about arthritis should be improved in order for nursing students to better understand everything related to arthritis.